Ethnocaring Model in Predicting Patient Satisfaction: How Powerful Is It? - Novian Mahayu Adiutama; Wardah Fauziah (Babali Nursing Research, 2022)
Introduction: Caring is the most important to get patient satisfaction. However, currently caring is only considered as empathy without regard to the patient's cultural background. This study aims to investigate patient satisfaction regarding nursing services in a multicultural area by using the ethnocaring model as a predictor. Methods: A cross-sectional study was conducted on patients in a nursing service in Subang District (n = 135 using consecutive sampling). Maintaining beliefs (MB), culture care preservation (CP), knowing (KN), being with (BW), negotiating (NE), doing for (DF), enabling (EN), and restructuring (RE) are used as independent variables, and patient satisfaction (PS) as the dependent variable. The instrument used was developed in accordance with ethnocaring model and PSQ-18. Multiple linear regression was used to analyze the ability of the ethnocaring model as a predictor of patient satisfaction. Results: The results showed that patient satisfaction had a mean score of 14.42 (score interval = 0-18). The following are the p-values for each variable: MB (0.021); CP (0.032); KN (0.015); BW (0.038); NE (0.026); DF (0.033); EN (0.043); and RE (0.034); they can all significantly predict PS with R-Square = 0.815. Conclusion: The strength of the ethnocaring model in predicting patient satisfaction was 81.5%. The construct of ethnocaring model could help nurses in understanding patient satisfaction.